Kształtowanie się pierwszej gminy muzułmańskiej w Mekce - Starosta, Bernard (Śląskie Studia Historyczno-Teologiczne, 1968)
Muhammad appears in the history not only as the creator of a new Islam religion. He appears also as an organizer and leader of the moslem community — umma. In his public activity he has been able to unite the nomadic Arabian tribes and to form a close state with regard to religion and politic, based on theocratic organization. In order to form the first moslem community Muhammad started his activity in Mecca in the years 610–622. Although he just became famous in the territory of Medina as a good politician, legislator, organizer and leader, we may admit, basing on the opinions of contemporary experts of this problem, that already in Mecca, proclaiming himself as a prophet and God's messenger, he had the intention to form a community consisting of believers in one God. In the first years of his activity in Mecca he did not attain good results. His rigoristic monotheism has been accepted negatively by the rearch citizens of Mecca who, in the actual relations, have been gaining profits from the cult of pagan Gods, existing in their city. Among his followers, besides few important citizens of the city, there were poor people and slaves. Muhammad organized his first community basing on quite new principles. Till Muhammad's appearence the Arabians did not create higher forms of state. They have had a tribe organization. The uniting factor for the Arabians has been the tradition of common descent. Forming his community Muhammad has broken with the old tribe organization. The uniting factor for his followers has not been the bond of blood but common worship of one God. The bond of blood, on which the Arabian tribe organization has been based Muhammad has substituted by a religion determining not only the duties of the community member but also regulating the total collective life. In autumn 622 it has come to formal breaking of the bonds with his native city and with the former tribe and race community. At that time Muhammad, with the group of his belivers, has moved to Medina. The moving to Medina has been called — hidjra. Hidjra has been very important in the further history of the moslem community and iniciated a new moslem era, existing in the Islam countries to the present time.